Numerical and Experimental Analysis of Seismic Soil Pile Structure Interaction - Ramazan Borujerdi, Ali (Emerging Advances in Integrated Technology, 2023)
The fundamental design of the piles is finished by static analysis, but particularly in seismically dynamic locales, the last configuration requires dynamic study. Dynamic soil-pile-structure interaction analyses require the stress-strain conduct of soils under dynamic loading conditions. The material nonlinearity can be addressed by comparable linear or completely nonlinear strategies. The correlation of these methodologies in the free-field site reaction analyses has been concentrated in recent years. In any case, the impacts on the soil-pile-structure interaction analyses have not been illustrated. In this study, a well-known centrifuge test was demonstrated and analyzed in the frequency domain (ACS SASSI) and in the time-domain (FLAC 3D) for equivalent-linear and fully nonlinear methods, respectively. The soil space was displayed with solid components in the projects, while the structural beam elements were utilized for the pile and the superstructure. The scaled speed acceleration time history of the Kobe earthquake was applied to the lower part of the soil-pile-structure model, and the acceleration-time histories were acquired at the ground surface and the superstructure. The outcomes obtained from the ACS SASSI and the FLAC 3D were compared with the centrifuge test. As per the outcomes, the peak ground and the superstructure accelerations were close to the experimental outcomes; however, the periods at the peak spectral accelerations were slightly different from the test results. The difference is more pronounced in SASSI than in FLAC, which may be attributed to the solution methods. Apart from the solution methods, the difference might be the inability to fully simulate the complex centrifuge test.